Biosurfactant Produced by Salmonella Enteritidis SE86 Can Increase Adherence and Resistance to Sanitizers on Lettuce Leaves (Lactuca sativa L., cichoraceae) - Rossi, Eliandra M.; Beilke, Luniele; Kochhann, Marília; Sarzi, Diana H.; Tondo, Eduardo C. (Frontiers in Microbiology, 2016)
Salmonella Enteritidis SE86 is an important foodborne pathogen in Southern Brazil and it is able to produce a biosurfactant. However, the importance of this compound for the microorganism is still unknown. This study aimed to investigate the influence of biosurfactant produced by S. Enteritidis SE86 on the adherence to slices of lettuce leaves and on the resistance to sanitizers. First, S. Enteritidis SE86 was inoculated on lettuce leaves in order to determine the amount of biosurfactant produced. Subsequently, S. Enteritidis SE86 was inoculated on lettuce leaves, with and without the biosurfactant, and the adherence and bacterial resistance to different sanitization methods were evaluated. S. Enteritidis SE86 produced biosurfactant after 16 hours (emulsification index of 11 to 52.15%) and showed greater adherence capability and resistance to sanitization methods when the compound was present. The scanning electron microscopy demonstrated that S. Enteritidis was able to adhere, form lumps, and invade the lettuce leaves stomata in the presence of biosurfactant. Results indicated that the biosurfactant produced by S. Enteritidis SE86 contributed to the adherence and increased the resistance to sanitizers when the microorganism was present on lettuce leaves.